Exploring Innovative Practices of Arabic Language Teachers in Developing Creative Learning at Madrasah Aliyah - Rohanda Rohanda; M. Fauzan Afsar; Muhammad Syafiq Ziyad (Gunung Djati Conference Series, 2026)
This study aims to identify the forms of innovative practices implemented by Arabic language teachers in the learning process at Islamic Senior High Schools (MA); to examine the factors that encourage teachers to develop creative learning; to analyze the strategies used by teachers to integrate methods, media, and technology in creating creative learning; to explore the challenges faced by Arabic teachers in applying innovative practices; and to understand how they overcome these challenges in MA. This research employs a descriptive qualitative approach to provide an in-depth depiction of the innovative practices of Arabic language teachers in MA. Primary data were obtained through interviews, observations, and documentation, while secondary data were collected from lesson plans (RPP), modules, and school policies. Data collection techniques included observation, semi-structured interviews, and document analysis. The interactive Miles and Huberman analysis model was used, through data reduction, data display, and conclusion drawing, supported by triangulation to ensure valid and comprehensive findings. The results indicate that innovation among Arabic language teachers in MA emerges from their ability to combine interactive methods, creative media, and digital technology to create communicative and contextual learning. These innovations are driven by professional motivation, students’ learning needs, 21st-century curriculum demands, and technological developments. Challenges such as low digital literacy, limited facilities, low student motivation, and administrative workload are addressed through professional training, collaboration, the use of alternative media, and the creation of supportive learning environments. Teachers play a key role as agents of instructional change.